Chemical and isotopic (H, O, S, and Sr) analyses of groundwaters in a non-volcanic region, Okayama prefecture, Japan: Implications for geothermal exploration. (March 2021) - Komatsu, Shinji; Okano, Osamu; Ueda, Akira
Highlights: Chemical and isotopic (D, O, S, and Sr) compositions of thermal and cold waters in Okayama were investigated. The geochemical characteristics of geothermal resources in a non-volcanic region were examined. The estimated underground temperature was approximately 100 °C at its maximum. Utilization of these geothermal resources for geothermal heat pumps was judged to be effective. Abstract: The chemical and D, O, S, and Sr isotopic composition of 26 thermal waters (>25 °C) and 25 cold waters from springs and wells in Okayama Prefecture were investigated to examine the geochemical characteristics of the geothermal resources in a non-volcanic region. No clear geochemical difference was noted between the thermal and cold waters. Some of these waters were formed by mixing of fossil seawater and meteoric water; however, most with low salt concentrations are of meteoric origin and are presumed to have flowed out with a residence time of several months. The waters studied were classified as Ca 2+ −HCO3 − and Na + −HCO3 − types, with 87 Sr/ 86 Sr values close to those of the granite base. These thermal and cold waters were formed by an infiltration of meteoric water into the granite layer that subsequently reacted with carbonate and clay minerals. Considering the main chemical components of the waters, the estimated maximum underground temperature was approximately 100 °C. Therefore, the utilization of these geothermal resources for geothermal heat pumps was judged to be effective even though calcium carbonate scale could precipitate in the heat exchanger.